Between the Traditional and the Modern: A Critical Discourse Analysis of Fatima Mernissi’s Dreams of Trespass: Tales of A Harem Girlhood (1995) - Restiwi, Siti (2011)
The aims of the research are for explaining, informing, telling, describing, discussing and guiding to other people towards what the writer’s opinion and dominant ideology. The research purposes to examine how the conflicts between the traditional and the modern values reflected in Fatima Mernissi’s memoir The Dreams of Trespass: Tales of A Harem Childhood published in 1995 by using critical discourse analysis a theory composed by Teun A. van Dijk. The type of this research is descriptive qualitative research. The method of collecting data is observation and analyzing the memoir as the object by exploring the structural components of it which can be revealed the dominant ideology reflected in this memoir. The result of the research shows the following conclusions. Firstly, based on the structural elements of the memoir, it is evident that the memoir is ideologically controlled and shows polarization between in-group and out-group positive selfrepresentation. Secondly, the dominant ideology of the memoir is liberal feminism suggesting the individual freedom represents a personal right that needs to be fulfilled for the goodness of social life.